2013
DOI: 10.1039/c3dt32740j
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and antiparasitic activity of aryl- and ferrocenyl-derived thiosemicarbazone ruthenium(ii)–arene complexes

Abstract: A series of aryl-functionalized and ferrocenyl monothiosemicarbazone compounds (L1-L4) were synthesized in moderate yields via a general Schiff-base condensation reaction. The thiosemicarbazone (TSC) ligands were reacted with the ruthenium dimer [Ru(Ar)(μ-Cl)Cl](2) (Ar = benzene; p-cymene) to yield a series of cationic mononuclear ruthenium(II)-arene thiosemicarbazone complexes of the general type [Ru(Cl)(TSC)(Ar)]Cl (1-8). The thiosemicarbazone ligands act as bidentate chelating ligands that coordinate to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 67 publications
8
66
0
Order By: Relevance
“…Furthermore the distances between metal and centroid of arene/Cp* ring are in range 1.678-1.797 Å , while the M-Cl bond lengths are in the range of 2.3932-2.4212 Å . Both sets of values are close to those found in related complexes reported in the literature [28][29][30][31][32].…”
Section: Molecular Structural Studiessupporting
confidence: 88%
“…Furthermore the distances between metal and centroid of arene/Cp* ring are in range 1.678-1.797 Å , while the M-Cl bond lengths are in the range of 2.3932-2.4212 Å . Both sets of values are close to those found in related complexes reported in the literature [28][29][30][31][32].…”
Section: Molecular Structural Studiessupporting
confidence: 88%
“…We found that incorporating organometallic fragments into the thiosemicarbazone scaffold resulted in a complex that exhibited moderate activity against Trypanosoma cruzi and M. tuberculosis strains. In addition, Chibale and co-workers described the synthesis and antimalarial evaluation of palladium (II), ruthenium (II) and gold (III) complexes containing ferrocenyl thiosemicarbazones [38,40,41]. In all cases, the heterobimetallic complexes exhibited moderate activity against chloroquine-susceptible (NF54) and chloroquineresistant (Dd2) Plasmodium falciparum strains.…”
mentioning
confidence: 97%
“…Beckford and co-workers have reported the Ru(II)-arene half-sandwich complexes with TSC ligands combining the {(η 6 -p-cymene) Ru(II)} moiety with TSC derivatives as ligands and further confirmed the good anticancer activity of these complexes against different human cancer cell lines [6,7]. Smith et al demonstrated the cytotoxicity and antiparasitic activity of a series of TSC derivatives and their corresponding mononuclear and dinuclear Ru(II)-arene complexes [8,9]. Su et al have synthesized some Ru(II)-arene complexes with TSC ligands and further investigated the anticancer activities of them [10,11].…”
Section: Introductionmentioning
confidence: 82%
“…Recently, Ru(II)-arene complexes of thiosemicarbazone (TSC) with half-sandwich-type structure have emerged as novel strategies to develop promising lead Ru-based therapeutic drugs [1][2][3][4][5]. Some research has demonstrated the anticancer activity of Ru(II)-arene complexes of TSC anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%